Novel aryl(heteroaryl)-substituted (pyrimidyl)benzamide-based BF2 complexes: Synthesis, photophysical properties, BSA-binding, and molecular docking analysis. (February 2019) - Bonacorso, Helio G.; Calheiro, Tainara P.; Acunha, Thiago V.; Iglesias, Bernardo A.; Franceschini, Steffany Z.; Ketzer, Alex; Meyer, Alexandre R.; Nogara, Pablo A.; Rocha, João B.T.; Zanatta, Nilo; Martins, Marcos A.P.
Abstract: This paper presents a new family of pyrimidine-based BF2 complexes. The series contains six examples of 1, 1-difluoro-3-aryl(heteroaryl)-1 H -pyrimido[1, 2- c ][1, 3, 5, 2]oxadiazaborinin-9-ium-1-uides (2 ) — in which aryl(heteroaryl) = phenyl, 4-MeC6 H4, 4-N(CH3 )2 C6 H4, 4-NO2 C6 H4, 2-naphthyl, and 2-thienyl. The heterocycles2 were easily synthesized at yields of 50–68% from reactions — at room temperature for 24 h — of simple N -(pyrimidin-2-yl)benzamides (1 ) with BF3 ·Et2 O, and they were fully characterized by 1 H-, 13 C-, 19 F, 11 B-NMR, GC–MS, and X-ray diffractometry. Moreover, the photophysical properties, TD-DFT analysis, BSA-binding experiments, and molecular docking studies for the new organoboron complexes2 were determined, presented, discussed, and compared with similar compounds that have already been described. Graphical abstract: Highlights: A series of novel pyrimidine-based BF2 complexes is synthesized and studied. Multinuclear NMR and X-ray diffraction data are used for structural elucidation. UV–vis, fluorescence, quantum yield and Stokes shift are presented and discussed. Bio-interaction results as BSA-binding studies and molecular docking are reported.